Multimodal Irregular Self-Selection in Chinese Postgraduate English as a Foreign Language Learners’ Conversation: When, How, and Why - Ji, Mengmeng; Zhang, Huiping (Frontiers in Psychology, 2022)
Irregular self-selection is a demonstration of active involvement in interaction. English as a foreign language (EFL) learners’ talk-in-interaction is one of such cases. Yet little research has explored when, how, and why learners implement this action. The aim of this paper is to address these issues in Chinese postgraduate EFL learners’ conversation from the perspective of multimodal interaction. To this end, we provide descriptive statistics and use multimodal conversation analysis to investigate the detailed process of irregular self-selection. The results show the interactional sensitivity of learners, and all the successful irregular self-selection can be divided into three types: Turn interruption, turn competition, and turn holding abortion. Learners implement this action by using multimodal resources, including lexis, syntax, pitch reset, intensity enhancement, gaze and so forth; however, their body movements lack diversity, causing behaviors to be constrained and inactive. The main purpose of irregular self-selection is to provide knowledge that contributes to the topical development. This study reveals that Chinese postgraduate EFL learners are interactionally competent members. They are able to achieve communicative goals but in a low diversity of body movements. The findings help to understand the detailed process of speakership claiming in EFL learners’ conversations.